Analysis of wheat production in the Republic of North Macedonia from 2016-2019 - Angeleska Aleksandra (Naučno društvo agrarnih ekonomista Balkana, Beograd; Institut za ekonomiku poljoprivrede, Beograd i Akademija ekonomskih nauka, Bukurešt, 2021)
Corn, wheat and other different types of cereal crops, are one of the basic nutritional products in general, which have essential and vast application in the daily diet of people around the world. Cereal crops are the most important food sources, and cereal-based food is the main source of energy, protein, B vitamins and minerals for the world population. Therefore, the goal of this research is to analyze the production of wheat on arable land in the Republic of North Macedonia, as an agricultural country, which will indirectly help to draw conclusions about the impact on the economic structure of the population, their standard of living, the investment and economic fluctuations in market prices, taken as a sui generis element, set as an assumption ceteris paribus against the other determinants and factors that affect the national economy in the Republic of North Macedonia.